Efeito do feedback extrínseco na cinemática de membro inferior e tronco durante um salto do ballet clássico: ensaio clínico controlado randomizado cego - Cabral, Anelise Moreti (Universidade Federal de São Carlos, 2019)
Classical ballet practice is associated with high prevalence of jump-related injuries, specially affecting the lower limbs. Different modalities of augmented feedback have been investigated in a variety of sports activities aiming at enhancing biomechanical parameters during risky movements. Nevertheless, studies analysing the effect of augmented feedback during classical ballet movements are still scarce. The aim of this study was to evaluate the effect of a multimodal augmented feedback session on lower limb and trunk kinematics during a classical ballet jump. Thirty-six amateur ballet dancers were randomly assigned to either a control group (CT, n = 18) to receive a brief warm-up session or an augmented feedback group (AF, n = 18) to receive, in addition to a brief warm up session, a combined visual feedback session associated with verbal instruction. Hip kinematics in the frontal and transversal planes and knee and trunk kinematics in the frontal plane were analysed at baseline (T1), immediate post-intervention (T2) and one-week post-intervention (T3). The effects of the intervention were analysed using a two-way, mixed model, repeated-measures analysis of variance. There was a trend for a group-by-time interaction for knee kinematics in the frontal plane in the preparation phase of the jump. At T2, participants in the AF group had increased peak knee adduction compared to participants in the CT group (MD = 2.61º; 95%CI = -0.08º-5.30º; P = 0.057; ηG² = 0.07). No interaction effects were observed for the other kinematic variables. A brief visual augmented feedback session associated with verbal instruction did not improve lower limb and trunk kinematics during a classical ballet jump. Therefore, this intervention should not be used in isolation as a strategy to improve jump-related kinematics in classical ballet dancers.
Effect of augmented feedback on lower limb and trunk kinematics during a classical ballet jump: a single-blind, randomized controlled trial
Keywords: Fisioterapia; Reabilitação; Dança; Joelho; Physiotherapy; Rehabilitation; Dance; Knee; Rehabilitación; Baile; Rodilla; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL